Biofuel Sustainability Requirements - The Case of Rapeseed Biodiesel - Franziska Junker; Alexander Gocht; Sandra Marquardt; Bernhard Osterburg; Heinz Stichnothe (German Journal of Agricultural Economics (GJAE), 2015)
Biodiesel production in Europe and Germany relies heavily on rapeseed oil. Thus, the biodiesel industry has become the most important outlet for rapeseed oil. In light of the increasing greenhouse gas (GHG) saving requirements at the European level, this situation may change: according to the default values specified in the current legislation, biodiesel produced from rapeseed oil will not meet GHG saving requirements as of 2017. In this article, we assess the market impacts of the withdrawal of rapeseed oil from the biodiesel industry in Germany and Europe. Simulations with the MAGNET and CAPRI modelling systems indicate a decline in producer prices for rapeseed of approximately 17% in the EU. The area dedicated to rapeseed production will decline by 6%. Rapeseed oil is primarily substituted by imported vegetable oils. Simultaneously, imports of biodiesel from North America, Argentina and Asia are projected to increase. We investigate options to improve the GHG balance of rapeseed biodiesel. We conclude that only a combination of climate-friendly produced fertiliser and efficient conversion processes can provide the necessary GHG emission-savings to meet the EU's sustainability goals after 2017.
Keywords: 330